Complex mantle flow beneath the Luxi uplift segment of the Tanlu fault zone inferred from SKS splitting measurements - Lu, Mingwen; Lei, Jianshe (Frontiers in Earth Science, 2023)
To better understand the anisotropic structure and mantle dynamics in and around the Luxi uplift segment of the Tanlu fault zone in East China, we collect waveform data recorded at 47 NCISP (Northern China Interior Structure Project) portable seismic stations during November 2000 to August 2001. Using the minimum transverse energy grid-search method of SKS wave splitting measurement, effective splitting results at 35 stations are obtained. Our results show that the fast wave polarization direction (FPD) in the study area is dominated by a nearly E-W direction, with a range of 70°-116° and an average FPD of N98°E, which is generally perpendicular to the trend of the Tanlu fault zone. The splitting time varies from 0.6 to 1.5 s with an average of 0.94 s. Although there are subtle differences in FPDs of different tectonic units, it is still evident that larger splitting times amounting to ~1.2 s are located north of the Luxi uplift, which is closely associated with the E-W horizontal flow in the big mantle wedge (BMW). In contrast, smaller splitting times are visible between the two branches of the Tanlu fault zone, indicating the existence of upwelling flow in the BMW. These complex mantle flow suggests that the BMW structure has played an important role in the deep dynamic processes beneath East Asia.